Local Area Network Interconnection - Onvural, Raif O.; Nilsson, Arne (Springer US, 1993)
There are many exciting trends and developments in the communications industry, several of which are related to advances in fast packet switching, multi media services, asynchronous transfer mode (ATM) and high-speed protocols. It seems fair to say that the face of networking has been rapidly changing and the distinction between LANs, MANs, and WANs is becoming more and more blurred. It is commonly believed in the industry that ATM represents the next generation in networking. The adoption of ATM standards by the research and development community as a unifying technology for communications that scales from local to wide area has been met with great enthusiasm from the business community and end users. Reflecting these trends, the technical program of the First International Conference on LAN Interconnection consists of papers addressing a wide range of technical challenges and state of the art reviews. We are fortunate to have assembled a strong program committee, expert speakers, and panelists. We would like to thank Professor Schwartz for his keynote speech. We would like to thank Professor Yannis Viniotis and his students for the preparation of the index. We gratefully acknowledge the generous financial support of Dr. Jon Fjeld, Mr. Rick McGee, and Mr. David Witt, all of IBM-Research Triangle Park. We also would like to thank Ms. Mary Safford, our editor, and Mr. John Matzka, both at Plenum Press, for the publication of the proceedings